2023
DOI: 10.1101/2023.02.15.528772
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for an aquatic origin of influenza virus and the orderArticulavirales

Abstract: The emergence of novel disease-causing viruses in mammals is part of the long evolutionary history of viruses. Tracing these evolutionary histories contextualises virus spill over events and may help to elucidate how and why they occur. We used a combination of total RNA sequencing and transcriptome data mining to extend the diversity and evolutionary history of the order Articulavirales, which includes the influenza viruses. From this, we identified the first instance of Articulavirales in the Cnidaria (inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Teleost fishes, the largest clade of living vertebrates that display extensive ecological diversity, are among those groups that naturally exhibit highly diverse viromes, making them an informative model system for determining the host and virological factors that impact crossspecies virus transmission 10,11 . Indeed, relatives of coronaviruses, hepatitis C virus, influenza viruses, filoviruses, and paramyxoviruses have all been identified in teleosts 2,[10][11][12][13][14][15] .…”
mentioning
confidence: 99%
“…Teleost fishes, the largest clade of living vertebrates that display extensive ecological diversity, are among those groups that naturally exhibit highly diverse viromes, making them an informative model system for determining the host and virological factors that impact crossspecies virus transmission 10,11 . Indeed, relatives of coronaviruses, hepatitis C virus, influenza viruses, filoviruses, and paramyxoviruses have all been identified in teleosts 2,[10][11][12][13][14][15] .…”
mentioning
confidence: 99%
“…Essentially, the evolution of RNA viruses that cause human disease is complex because various RNA viruses that infect humans are not limited to mammals, but closely related RNA viruses also exist in fish [ 7 ]. Indeed, a recent study revealed fish could be the first host of the genus influenza virus that also infects humans [ 35 ]. Further RNA virome studies will reveal the diversity and evolution of RNA viruses that cause human diseases, including SARS‐CoV‐2.…”
Section: Sars‐cov ‐2 Related Rna Viromementioning
confidence: 99%
“…The sequence accessions for the viruses identified here through data mining are provided in SI Appendix . The multiple sequence alignments used to generate all of the phylogenetic trees presented in this study are freely available at https://github.com/mary-petrone/ancient_articulavirales ( 56 ).…”
Section: Data Materials and Software Availabilitymentioning
confidence: 99%